On the comics-nature of the Codex Seraphinianus. Issue 1 (1st July 2015) - Davies, Paul Fisher
Italian architect Luigi Serafini's wildly inventive and anarchic Codex Seraphinianus has been entertaining and confusing readers since its publication in the early 1980s. It purports to be a 'found manuscript' akin to the Voynich manuscript, written in an alien but tantalizingly familiar-seeming language, and its small print runs and beautiful volumes have made it an object of desire and intrigue. Attempts have been made to decipher the text and numerals, and thereby to 'read' the book, but readers have been kept guessing. Serafini has revealed that the text itself is meaningless; but nonetheless the book is in many senses 'readable'. In what ways can this be done? This article will argue that the text relies on conventions of comics and graphic novels to become accessible despite the alienness of its content; that whilst the 'words' have no semantics and no grammar, the text as a whole has a discourse structure, and shares a textual logic with comics that carries the sense that readers can make of it. This 'comics-nature' is the key to reading the Codex Seraphinianus. Such an exploration of how the Codex may be read as a comic can reveal to us some of the qualities of that comics-nature itself, and shed light on the reading approaches that readers take to graphic narrative in more familiar forms too.